LGL leukemia patients exhibit substantial protective humoral responses following SARS‐CoV‐2 vaccination. Issue 3 (31st May 2022) - Cheon, Heejin; Elghawy, Omar; Shemo, Bryna C.; Feith, David J.; Loughran, Thomas P.
Abstract: Large granular lymphocyte leukemia is a rare chronic lymphoproliferative disorder of cytotoxic cells. Other hematological malignancies such as CLL and multiple myeloma have been associated with poor vaccination response and markedly increased severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) mortality rates, specifically in patients who have undergone immunosuppressive therapy. Given the immunosuppressive therapies often used to treat the disease, large granular lymphocytic (LGL) patients may be especially vulnerable to SARS‐CoV‐2 infection. A questionnaire was sent to all patients in the LGL Leukemia Registry at the University of Virginia (UVA) to obtain information on vaccination status, type of vaccine received, side effects of vaccination, patient treatment status before, during, and after vaccination, antibody testing, history of coronavirus disease 2019 (COVID‐19) infection, and presence or absence of booster vaccination. Antibody testing of 27 patients who had quantitative SARS‐CoV‐2 Spike Protein IgG levels determined by University of Virginia medical laboratories via the Abbott Architect SARS‐CoV‐2 IgG II assay were collected. The assay was scored as reactive at a threshold of ≥50.0 AU/mL or nonreactive with a threshold of <50.0 AU/mL. LGL patients without treatment as well as patients who held treatment prior to their vaccination have a robust humoral response to SARS‐CoV‐2 vaccines. Patients who did not hold their immunosuppressive treatments have signifigantly diminished vaccine response compared to those who held their immunosuppressive treatment. Our findings support a dual strategy of pausing immunotherapy during the vaccination window and administration of the SARS‐CoV‐2 booster to all LGL leukemia patients to maximize protective antibodies.